PENGEMBANGAN SOEMOLI (SMART OSING EDUCATION MONOPOLI GAME) BERBASIS WEBSITE DALAM MENINGKATKAN WAWASAN PARIWISATA, BUDAYA DAN BAHASA OSING BANYUWANGI PADA MIS SUNAN AMPEL - Octavian Damai Putri; Istikoma Istikoma; Irhas Wahyu Ningtyas; Dhina Rohmawati; Bunga Nailah Salsabilah; Ika Yuniwati; I Wayan Suardinata (Jurnal Abdimas Bina Bangsa, 2023)
The development of science and technology is increasingly intense to affect various sectors, especially in the field of education. As a result, learning media is required to be of quality and innovate. Banyuwangi Regency is an area rich in culture, tourism and has a regional language, namely Osing language. The majority of MIS Sunan Ampel students actively use osing language as a daily language. However, in the knowledge of osing language values, MIS Sunan Ampel students are considered quite low. The contributing factor is MIS osing language subjects for two years. This is due to the absence of effective learning media during a pandemic. Therefore, online learning media is needed. The stages of this activity start from the development of the SOEMOLI Website (Smart Osing Education Monopoly Game) to student assistance. The results obtained from student mentoring, student interest increased by 25 points, knowledge of the osing language increased by 20 points, cultural understanding and tourism increased by 45 points. So it can be concluded that SOEMOLI is quite effective